Consistency is key in online learning: Evaluating student and instructor perceptions of a collaborative online-course template. Issue 3 (October 2019) - Scutelnicu, Gina; Tekula, Rebecca; Gordon, Beth; Knepper, Hillary J
This study examines the features and benefits of a collaborative online-course template designed for and used by the department of public administration program at a mid-Atlantic university in the USA. Drawing on a multi-informant original survey addressed to students and faculty the study aims to answer the question: to what extent are online-course templates beneficial to student learning and instructor teaching experiences? Findings suggest that, overall, both students and faculty had positive perceptions of the template's consistency in terms of format and access, but students found the template to be more beneficial to their learning than did faculty to their teaching.